2011
DOI: 10.1016/j.neubiorev.2010.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Glucose enhancement of human memory: A comprehensive research review of the glucose memory facilitation effect

Abstract: The brain relies upon glucose as its primary fuel. In recent years, a rich literature has developed from both human and animal studies indicating that increases in circulating blood glucose can facilitate cognitive functioning. This phenomenon has been termed the 'glucose memory facilitation effect'. The purpose of this review is to discuss a number of salient studies which have investigated the influence of glucose ingestion on neurocognitive performance in individuals with a) compromised neurocognitive capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
123
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(140 citation statements)
references
References 128 publications
(228 reference statements)
6
123
1
Order By: Relevance
“…These findings raise the possibility that the degree of mental effort required to complete a task, rather than hippocampal involvement, is the more important determinant of task sensitivity to glucose enhancement [28]. A corollary of this theory is that glucose may facilitate memory function by targeting brain regions more globally, with effects not strictly isolated to the hippocampus [10].…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…These findings raise the possibility that the degree of mental effort required to complete a task, rather than hippocampal involvement, is the more important determinant of task sensitivity to glucose enhancement [28]. A corollary of this theory is that glucose may facilitate memory function by targeting brain regions more globally, with effects not strictly isolated to the hippocampus [10].…”
Section: Introductionmentioning
confidence: 96%
“…A recent meta-analysis Hoyland et al [6] provided evidence to suggest that glucose may affect memory performance to a greater extent than other cognitive domains. While the exact mechanism by which glucose improves memory performance is yet to be elucidated, increased acetylcholine and insulin production and resultant effects on hippocampal function have emerged as important factors [3,[7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glucose appears to be especially important for hippocampal-dependent memory [90,91], and for demanding tasks [92][93][94]. After awakening, blood glucose levels in the brain are relatively low [88], and improvements in working memory have been demonstrated upon glucose administration -regardless of whether blood glucose levels were depleted upon time of administration [89].…”
Section: Glucosementioning
confidence: 99%
“…Particularly relevant to the present investigation, a large body of research has shown that glucose metabolism is important for one of the major elements of self-generated thought; episodic memory [13,14]. Impairments in episodic memory has been observed in healthy younger individuals with poor glucose regulation [15], in middle aged adults [16] and also poor gluco-regulating adolescents after consuming a glucose containing drink [17,18,19], in older adults with and without Mild Cognitive Impairment [20] and in those individuals with impaired glucose tolerance and diabetes (see [14,21] for reviews).…”
Section: Introductionmentioning
confidence: 99%